MONITORING OF PESTICIDE RESIDUES IN HUMAN MILK (Biological Sciences - PJSIR, 2003)
After establishing proper analytical methodology  for multiple  pesticide  residues,  cotton-growing  areas  of Multan  Divi sion of Pakistan were surveyed and 40 samples of human mi lk from cotton  pickers  were  collected  during  two  crop  seasons. Screening of these samples showed 72.5% contamination with 19 different pesticides/metabolites. The most  frequently occurring pesticides were DDT and its metabolites, dimethoate, cyhalothrin, monocrotophos, profenofos and quinalphos.